Indian Government Schemes Based Analysis on Women Empowerment in Financial Inclusion - Singh, Tanu; Pande , Sarveshwar (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2023)
In general Women belonging to villages tend to spend the maximum of their time in household activities without any hesitation. In return, they don’t receive any merits or credits from the family and society. This paper aims in conducting detailed research work based on, the understanding found among women folk belonging to lower-middle-class women and poor income about the need for financial inclusion. The study was carried out in Ludhiana, Punjab among women from low-income and lower-middle-class households. Out of 1000 approaches, 757 respondents replied (75%). Later the data were organized and analyzed for the results. To make the work stronger a conceptual framework was framed. The tests like one-way ANOVA and Post-Hoc tests were also carried out. The outcomes showed that there are major differences seen when women are empowered and occupied they are reflecting positively on financial inclusion.